Cloning and sequence analysis of three variants of the gene encoding alkaline xylanase C from the alkaliphilic bacillus sp (NCL 87-6-10) - Sharma, Poonam; Rele, Meenakshi V.; Kumar, Lalitha Sunil (Biochemical Genetics, 2013)
Alkaline xylanase C from the alkaliphilic Bacillus sp. (NCL 87-6-10) has a low molecular weight and alkaline pI and is cellulase-free, properties compatible with its use in the prebleaching of pulp. We report here the cloning and sequence analysis of three variants of the gene encoding xylanase C; xyl C1, xyl C2, and xyl C3. In phylogenetic analysis, the three xylanase C variants clustered into a single group along with other reported alkaline xylanases. Residues contributing to the alkaline pH were present in all three variants. DNA and protein sequence comparison of these variants with other reported alkaline xylanases revealed silent mutations, some of which are due to codon preference in the respective organisms. The recombinant Xyl C1 that was successfully expressed in E. coli BL21 (DE3) had properties similar to the native enzyme.
Keywords: Alkaline xylanase C; Alkaliphilic Bacillus sp (NCL 87-6-10); Cloning; E. coli BL21 (DE3) expression; Sequence analysis

Male biased gene flow in banana pseudostem weevil (Odoiporus longicollis Oliver) as revealed by analysis of the COI-tRNA(Leu) COII region - Shankar, Pallavi; Kulkarni, Vishvas M.; Kumar, Lalitha Sunil (Genetica, 2015)
The genetic diversity amongst thirty weevils representing six Indian populations of banana pseudostem weevil i.e. Odoiporus longicollis (Oliver) was estimated by sequence analysis of the partial COI-tRNA(Leu)-COII region. The sequences exhibited AT bias typical of insect mitochondrial DNA which was highest in the first codon position of COI and in the third codon position of COII. There was no phylogeographic distribution of the populations. The Fu and Li's D and F tests were non-significant for this mitochondrial region. No Wolbachia infection was detected in any of the populations. The genetic differentiation amongst the populations was highly significant (p < 0.001; chi(2) = 123.333; df = 75), suggesting restricted gene flow between the populations. This result did not correlate with that obtained with nuclear rDNA markers i.e. ITS1 and ITS2, suggesting a male biased gene flow between the populations.
Keywords: Banana pseudostem weevil; COI-tRNA(Leu) -COII; Genetic differentiation; Male biased gene flow; Odoiporus longicollis (Oliver)

Streptomyces lonarensis sp nov., isolated from lonar lake, a meteorite salt water lake in India - Sharma, Trupti K.; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Shinde, Vidhya K.; Zhan, Jing; Li, Wen-Jun; Rele, Meenakshi V.; Dastager, Syed Gulam; Kumar, Lalitha Sunil (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2016)
A novel alkaliphilic actinomycete, strain NCL716(T), was isolated from a soil sample collected from the vicinity of Lonar Lake, an alkaline salt water meteorite lake in Buldhana district of Maharashtra State in India. The strain was characterised using a polyphasic taxonomic approach which confirmed that it belongs to the genus Streptomyces. Growth was observed over a pH range of 7-11 at 28 A degrees C. The cell wall was found to contain ll-diaminopimelic acid and traces of meso-diaminopimelic acid. The major fatty acid components were identified as iso-C-16:0 (46.8 %), C-17:1 (12.4 %), anteiso-C-15:0 (5.1 %) and anteiso-C-17:1 (4.8 %). The major polar lipids were identified as diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and phosphatidylinositol. The major menaquinones were determined to be MK-9 (H-6) (70.3 %), MK-9 (H-4) (15.5 %) and MK-9 (H-8) (7.2 %). The G+C content of the DNA of the type strain was determined to be 71.4 mol %. The 16S rRNA gene sequence has been deposited in GenBank with accession number FJ919811. Although the 16S rRNA gene sequence analysis revealed that strain NCL716(T) shares > 99 % similarity with that of Streptomyces bohaiensis strain 11A07(T), DNA-DNA hybridization revealed only 33.2 +/- A 3.0 % relatedness between them. Moreover, these two strains can be readily distinguished by some distinct phenotypic characteristics. Hence, on the basis of phenotypic and genetic analyses, it is proposed that strain NCL716(T) represents a novel species of the genus Streptomyces, for which the name Streptomyces lonarensis sp. nov., is proposed. The type strain is NCL 716(T) (=DSM 42084(T) = MTCC 11708(T) = KCTC 39684(T)).
Keywords: Alkaliphile; DDH analysis; Polyphasic taxonomy; Streptomyces lonarensis sp nov.

Genetic variability in Indian populations of banana corm weevil [Cosmopolites sordidus (Coleoptera: Curculionidae)] assessed by RAPDs and AFLPs - Yadav, Sweta Kumari U.; Singh, Jyotsna; Padmanaban, B.; Kumar, Lalitha Sunil (International Journal of Tropical Insect Science, 2017)
Cosmopolites sordidus (Germar), commonly known as banana corm weevil, is an important economic pest in Asia that can cause severe yield loss depending upon the stage at which infestation occurs. In spite of its economic importance, little is known about the population structure of this pest in India. Random amplified polymorphic DNA (RAPD) and amplified fragment length polymorphism (AFLP) were used to characterize the population genetic structure of C. sordidus collected from five hot spot locations in India. Nineteen RAPD primers and five selective AFLP primer combinations generated 147 and 304 amplification products, respectively. UPGMA dendrograms generated with both marker systems failed to reveal populations clustered based on geographic distance, which was confirmed by the Mantel test, which did not show a strong correlation between genetic distance and geographic distance. Values of indices of genetic identity showed that the populations were closely related. Though the gene flow estimate (Nm) between the populations was 0.469, suggesting restricted gene flow, the populations are not genetically distinct. These observations suggest that the range expansion of this banana pest in India has taken place through transport of infested corms and plant material, resulting in genetically close populations that are geographically distinct. These results provide important information on the population structure of this pest in India, which will aid in designing suitable strategies for its control and management, especially with respect to insecticide resistance.
Keywords: Aflps; Arbitrary Primers; Bemisia-tabaci; Cosmopolites Sordidus; diversity; Genetic diversity; Germar Coleoptera; insecticide resistance; Markers; Musa Spp.; Pcr; Rapds; Restricted Gene Flow Natural-populations; Scirpophaga-incertulas

Analyses of the internal transcribed rDNA spacers (ITS1 and ITS2) of Indian weevils of Odoiporus longicollis (Olivier) reveal gene flow between locations - Kumar, Lalitha Sunil; Shankar, Pallavi; Kulkarni, Vishvas M. (International Journal Of Tropical Insect Science, 2018)
An important step towards developing a successful integrated pest management (IPM) programme for the control of banana pseudostem weevil, Odoiporus longicollis (Olivier), a serious pest of banana in India, is the study of the population structure of the pest. In the present study, the genetic variation among 30 individual weevils of O. longicollis collected from six different locations was assessed by analysing the primary nucleotide sequences of the rDNA ITS1 and ITS2 regions. AMOVA, Mantel test, and the maximum likelihood trees of the haplotypes failed to reveal any phylogeographic structuring, which was confirmed by haplotype analysis and genetic differentiation estimates. The results indicate that the locations are not differentiated, i.e. there is gene flow between the locations. The star-shaped networks revealed a signature of demographic expansion that was confirmed by the different demographic tests. These results provide important information, which is essential for the development of suitable strategies for the control of this banana pest, as well as management of its resistance to insecticides.

Secondary structure of the internal transcribed rDNA (ITS) regions of cosmopolites sordidus (Germar) and odoiporus longicollis (Olivier): a first report in family Curculionidae - Kumar, Lalitha Sunil (International Journal of Tropical Insect Science, 2019)
In the present work the consensus secondary structure of the internal transcribed rDNA spacers ITS1 and ITS2 of two weevils i.e. Cosmopolites sordidus (Germar) and Odoiporus longicollis (Olivier) has been described. The secondary structures of the ITS1 region of C.sordidus and O.longicollis have ten and five helices respectively, emerging from a central core. Two and five helices emerge from a central core in the ITS2 secondary structures of C.sordidus and O.longicollis respectively, and do not conform to the `paneukaryotic' four domain model. The ITS2 sequences of these two weevils share three regions with maximum sequence identity. Of these, two are present at the 5' and 3' end and share structural similarity, suggesting their possible role in the processing of the rRNA. This is the first report of the secondary structure of the ITS region in family Curculionidae which can serve as a valuable resource for homology modelling and phylogenetic studies.
Keywords: Cosmopolites sordidus (Germar); Curculionidae; ITS1; ITS2; Odoiporus longicollis (Olivier); Secondary structure